Doxa and related concepts in the fourth Gospel : an inquiry into the manifestation of Doxa in Jesus' cross - Van der Watt, J.G. (Jan Gabriel), 1952- (University of Pretoria, 2013)
Thesis (PhD (New Testament Studies))--University of Pretoria, 2008.